Current Treatment Approaches for Human Epidermal Growth Factor Receptor 2-Positive Breast Cancer in Adjuvant and Neoadjuvant Settings - Goyal, Pankaj; Doval, Dinesh Chandra; Agarwal, Chaturbhuj; Jain, Parveen; Chaudhari, Krushna; Domadia, Kshitij; Redhu, Pallavi; Koyyala, Venkata Pradeep Babu; Goel, Varun; Batra, Ullas; Talwar, Vineet; Bothra, Sneha (Indian Journal of Medical and Paediatric Oncology, 2021)
Breast cancer (BC) is the second most common cancer and the second leading cause of mortality among women globally. Approximately 20 to 25% of BC patients have amplification of the human epidermal growth factor receptor 2 (HER2) genes, a marker of poor prognosis. However, the introduction of anti-HER2-therapies (trastuzumab, followed closely by lapatinib, pertuzumab, trastuzumab emtansine, and neratinib) has changed the natural history of HER2-positive BC and improved the outcome in HER2-positive BC patients. The preeminence of anti-HER2 combination therapy in achieving complete inhibition of the various HER receptor dimers has been demonstrated in clinical studies. However, despite these therapeutic advances, tumors expressing estrogen receptor have poorer responses to targeted therapy and are more likely to relapse. A better understanding of resistance to existing anti-HER2 agents, along with the role played by the microenvironment and of interconnected signaling pathways, can permit tailor-made therapeutic options for each patient. This review aimed to evaluate treatment approaches for BC patients with HER2-positive disease in the adjuvant and neoadjuvant settings, also exploring the possibilities of extended duration of anti-HER2 maintenance therapy.
Keywords: adjuvant; human epidermal growth factor receptor 2 positive breast cancer; neoadjuvant